A Series on Diseases in the Florida Vegetable Garden: Squash - Pamela Roberts; Rosa Muchovej; Tom Kucharek; Ken Pernezny; Timur Momol (EDIS)
PP-239, an 8-page illustrated fact sheet by Pamela Roberts, Rosa Muchovej, Tom Kucharek, Ken Pernezny, and Timur Momol, describes microorganisms that cause plant diseases, including fungi, bacteria and viruses, plus specific squash diseases. Includes tips for disease prevention for squash. Published by the UF Department of Plant Pathology, September 2007.